2015
DOI: 10.1007/s10067-015-2975-1
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to strictly diagnose fibromyalgia syndrome in patients with chronic widespread pain?

Abstract: The applicability of the American College of Rheumatology (ACR) 1990 and 2010 criteria for the diagnosis of fibromyalgia syndrome (FMS) was determined in 284 patients with chronic widespread pain (CWP) including those with regional and systemic painful disorders. On the basis of initial evaluation, patients were classified into three groups. Group 1, those without any comorbid disease (N = 105), group 2, those having regional non-inflammatory painful disorders (N = 104), and group 3, those with a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…In non-nociceptive pain, my treatments of patients with FM and without FM are generally identical. The diagnostic criteria of FM are useful for diagnosis; however, they are not useful for treatment [56]. To put it briefly, I believe that the significance of the criteria is to identify uniform patients with FM in medical journals and/or medical meetings.…”
Section: Discussionmentioning
confidence: 99%
“…In non-nociceptive pain, my treatments of patients with FM and without FM are generally identical. The diagnostic criteria of FM are useful for diagnosis; however, they are not useful for treatment [56]. To put it briefly, I believe that the significance of the criteria is to identify uniform patients with FM in medical journals and/or medical meetings.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent study, Arzu Yagiz On and colleagues at Ege-University have also raised this issue [1] . They reported a survey of 284 patients with CWP, who had admitted to Physical Medicine and Rehabilitation, Algology and Rheumatology clinics of a university hospital.…”
Section: Research Highlightmentioning
confidence: 98%
“…My suggestion does not mean to ignore currently available diagnostic criteria for FMS. Previous studies, including ours demonstrated that the patients with CWP who had satisfied the TP criterion of the ACR 1990 seemed to have greater disease burden with more severe pain, more comorbidities and pain related medications, and worse overall health comparing to those who had not [1,[146][147][148][149][150][151] . In their recent study, Jimenez et al found that patients fulfilling the modified 2010 only had worse symptom profile than those fulfilling the 1990 criteria only [152] .…”
Section: Research Highlightmentioning
confidence: 99%
“…Bu gelişmeler ışığında artık, FMS'nin artık, santral sensitizasyona bağlı kronik yaygın ağrı spektrumunun en uç örneği kabul edilmesi gerektiği görüşü yaygınlaşmaktadır (17)(18)(19).…”
Section: Etiyoloji Ve Patogenezunclassified